IMPLEMENTASI KOMPETENSI MATA KULIAH PENDIDIKAN KEWARGANEGARAAN DI PERGURUAN TINGGI DALAM MENGHADAPI TANTANGAN GLOBALISASI - Febrian Alwan Bahrudin (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2019)
This research contained about the implementation of civic education competency in college; in order to face the globalization defiance, this research has done at Sultan Ageng Tirtayasa University. The aim of this research is to know how the implementation of civic competency that consist of civic knowledge, civic skill, and civic disposition. This research used qualitative features with descriptive methode, the result of this research shows that the implementation of civic education competency in order to face the globalization defiance can be happened by three steps. The first step is planning, in planning step, the civic education supporting lecturer made a study planner for every semester together that customized with regular requisite book from directorate general and student affairs of Ministry of Research, Technology and Higher Education of the Republic of Indonesia. In arrangement of civic education learning in college has the competency that must accomplished by students and the implementation which in civic knowledge. Student got the knowledge from lecturer through the process teaching and learning in class about the materials that already made based on the study planner for each semester. After the first competency, next to the second one which is civic skill. For this compentency, students had given the activity that could build their critical thinking. Project citizen, one of the activity that given to students to reach their more knowledge potentions, especially their skill as student college. The last competency is civic disposition, this competency is the result of mixed two competencies; citizenship knowledge and citizenship skill. From citizenship character competency, in hopes that the students could get the knowledge and skill that shows a good personality based on Undang-Undang Dasar 1945, so they will not easily get contaminated by the negative impacts of globalization.